2022
DOI: 10.3390/jcm11030837
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Iron Metabolism Proteins in Patients with Chronic Heart Failure

Abstract: In heart failure, iron deficiency is a common comorbid disease that negatively influences exercise tolerance, number of hospitalizations and mortality rate, and this is why iron iv supplementation is recommended. Little is known about the changes in iron-related proteins in the human HF myocardium. The purpose of this study was to assess iron-related proteins in non-failing (NFH) vs. failing (FH) human myocardium. The study group consisted of 58 explanted FHs; control consisted of 31 NFHs unsuitable for transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Serum levels of sTfR are increased in both patients with an absolute or functional iron deficiency, 43 , 67 since the receptor is upregulated in response to a decrease in cytosolic iron, regardless of cause. However, the failing heart often shows decreased expression of TfR1, 68 , 69 perhaps the result of neurohormonal activation, 70 , 71 which may contribute to an intracellular iron deficiency in cardiomyocytes. However, it is possible that this down‐regulation of TfR1 is modified into an upregulation of TfR1 when myocardial iron stores are depleted.…”
Section: Changes In Iron Homeostasis Proteins In Patients With Heart ...mentioning
confidence: 99%
“…Serum levels of sTfR are increased in both patients with an absolute or functional iron deficiency, 43 , 67 since the receptor is upregulated in response to a decrease in cytosolic iron, regardless of cause. However, the failing heart often shows decreased expression of TfR1, 68 , 69 perhaps the result of neurohormonal activation, 70 , 71 which may contribute to an intracellular iron deficiency in cardiomyocytes. However, it is possible that this down‐regulation of TfR1 is modified into an upregulation of TfR1 when myocardial iron stores are depleted.…”
Section: Changes In Iron Homeostasis Proteins In Patients With Heart ...mentioning
confidence: 99%
“…Furthermore, iron content was negatively correlated with myocardial ferritin, which suggests that iron deficiency was associated with disorders with myocardial iron storage. Further studies confirmed that the expression of total myocardial FT and the expression of individual components, FT-HC, FT-LC, and FT-MTC, were significantly reduced in the group of patients with advanced HF [ 102 ]. The results suggest more complicated relationships between iron transport and metabolism proteins in the failing heart than previously thought.…”
Section: Iron Metabolism In the Failing Human Heartmentioning
confidence: 93%
“…The results suggest more complicated relationships between iron transport and metabolism proteins in the failing heart than previously thought. In the iron-cell-transportation proteins, the expression of TfR1, the crucial transporter for iron uptake, was found to be reduced on the mRNA [ 42 ] and protein levels [ 102 ]. Moreover, the expression of transferrin-independent iron channels DMT-1 and L-CH were significantly reduced on the protein levels.…”
Section: Iron Metabolism In the Failing Human Heartmentioning
confidence: 99%
See 2 more Smart Citations